Secular trends of age at menarche and the effect of famine exposure on age at menarche in rural Chinese women - Xueyan Wu; Lei Bao; Zhen Du; Xiaotian Liu; Wei Liao; Ning Kang; Chunyang Sun; Tanko Abdulai; Zhihan Zhai; Chongjian Wang; Yuqian Li (Taylor & Francis Group, 2022)
Background Over the past few decades, more studies have suggested that the age at menarche (AAM) has continued to decline. However, the AAM for women in resource-constrained areas is not clear. Moreover, the association between the Chinese famine and AAM is still unclear in rural regions. Aim The study aimed to investigate the secular trends of AAM for women born between 1935 and 2000 and to further explore the effect of famine on AAM in rural China. Subjects and methods The study included 23,444 women participants from the baseline study of the Henan Rural Cohort study. Changing AAM over time was analysed using linear regressions. Multinomial logistic regression was conducted to analyse the association between famine exposure and AAM subgroups. Results The age-standardised mean AAM was 14.74 years. The average AAM declined from 16.98 years for those born in 1935 to 13.87 years for those born in 2000, a decline of 0.077 years per 1 year and 0.729 years per decade. Compared to the reference group, women exposed to famine during foetal, early childhood, middle childhood, and late childhood were 1.376 (95% CI = 1.071-1.769), 1.848 (95% CI = 1.512-2.259), 2.084 (95% CI = 1.725-2.518), and 2.146 (95% CI = 1.788-2.576) times more likely to be ≥18 years AAM than women unexposed to famine, respectively. Conclusion AAM showed a decreasing trend in rural China. Furthermore, both foetal and childhood famine exposure, especially in late childhood, were positively associated with increased AAM compared to unexposed famine.